Different endoscopic treatments for small colorectal polyps: A systematic review, pair-wise, and network meta-analysis - Li, Xuanhan; Zhu, He; Li, Fudong; Li, Ri; Xu, Hong (Frontiers in Medicine, 2023)
Background And Study Aims: In recent years, cold snare polypectomy (CSP) has been increasingly used for small polyps (<10 mm) instead of hot snare polypectomy (HSP). However, evidence-based research regarding the effectiveness and safety of CSP and HSP are still lacking. Additionally, for 4–10 mm non-pedunculated polyps, the polyp removal method is still controversial. Therefore, it is clinically significant to conduct pair-wise and network meta-analyses to assess such resection methods. Methods: We searched PubMed, Embase, and the Cochrane library for randomized controlled trials (RCTs). Only studies that involved the resection of polyps <10 mm were included. Outcomes included the complete resection rate, polyp retrieval rate, procedure-related complications, and procedure times. Results: Overall, 23 RCTs (5,352 patients) were identified. In meta-analysis compared CSP versus HSP for polyps <10 mm, CSP showed lower complete resection rate than HSP although with no statistically significant difference (odds ratio (OR): 0.77, 95% confidence interval (CI): 0.56–1.06). CSP showed a lower risk of major post-polypectomy complications compared to HSP (OR: 0.28, 95% CI: 0.11–0.73). In the network meta-analysis for 4–10 mm non-pedunculated polyps, HSP and endoscopic mucosal resection (EMR) showed a higher complete resection rate than CSP (OR: 2.7, 95% CI: 1.3–9.2 vs. OR: 2.6, 95% CI: 1.0–10). Underwater CSP ranked third for complete resection with no complications. Conclusion: For <10 mm polyps, CSP is safer than HSP, especially for patients taking antithrombotic drugs. For 4–10-mm non-pedunculated polyps, HSP and EMR have higher complete resection rates than CSP.